Penyuluhan Gizi Terhadap Tingkat Pengetahuan Jajan Anak Sekolah Dasar - Sunarto Sunarto; Mustamin Mustamin; Nur Wahidah Apriani (Direktorat Politeknik Kesehatan Makassar, 2024)
Consumption of unhealthy snacks in children is caused by a lack of knowledge about healthy snacks. Consumption of snacks is something that is characteristic of children. Snacks that are bought by children are often not considered either in terms of cleanliness or the ingredients in these foods. This study is to determine the level of knowledge to determine the level of knowledge of school children's snacks before and after counseling, to determine the level of school children's snacking habits, and to analyze the effect of nutrition counseling on the level of knowledge of elementary school children's snacks. The design of this study is a pre-experimental study with a one group pre-test and post-test design at SD IT Al-Fikri Makassar in 2023. The population is students in grades 4, 5 and 6. The sample size is 59 people. Knowledge and eating habits are known by giving questionnaires to students. Statistical test with paired test T test. The study found that the sample was generally class 6B (37.3%), 11 years old (28.8%), 24 women (40.7%) and 35 men (59.3%). The level of knowledge before and after counseling was good (52.5%) and (84.7%). The habit of snacking before and after counseling is good (47.5%) and (44.1%). Statistical analysis revealed that there was an effect of counseling with a value of p = 0.000. There was no effect of counseling with p value = 0.281. There was an effect of counseling on the level of knowledge of elementary school children's snacks before and after counseling. There was no effect of counseling on snack habits of elementary school children. There was an effect of nutrition counseling on the level of knowledge of snacks of elementary school children. For students who have knowledge of snacks in the good category so that they remain clever in choosing snacks at school. It is expected that teachers will monitor the habits of snacks and food sold in school canteens and food vendors in the school environment so that students do not consume snacks carelessly to prevent health problems. For students who have a habit of snacking in the good category to maintain these habits.